Democratic Leadership and Work Motivation as Drivers of Employee Performance - Roayani; Editya Nurdiana (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the effect of democratic leadership and work motivation on employee performance in the Cirebon City Satpol PP. The research was motivated by performance challenges such as low discipline, delays in task completion, and limited innovation, which reduce organizational efficiency. The objective is to analyze the individual and combined effects of leadership and motivation on performance. A quantitative, cross-sectional survey was conducted using total sampling of eligible employees. Data were collected through Likert-scale questionnaires and analyzed using multiple regression after classical assumption tests. Findings reveal that both democratic leadership and work motivation have positive and significant effects on performance, with motivation exerting a stronger influence than leadership. Together, these variables explain a substantial proportion of performance variance. The study concludes that participatory leadership and well-designed motivation strategies are effective managerial tools for improving productivity and efficiency in public organizations without increasing fiscal burden. These results contribute to management science and behavioral economics by demonstrating how non-financial interventions can optimize resource utilization in government institutions.